IJABE Guidelines for Authors - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2013)
1 About IJABE2 Criteria for Publication3 Journal Manuscript Format4 Pre-submission Enquiries5 Submissions6 Peer-Review & Editorial Process